The Health Benefits and Functional Properties of Gochujang: A Comprehensive Review of Fermentation and Bioactive Compounds - Young Kyoung Park; Jinwon Kim; Myeong Seon Ryu; Hee-Jong Yang; Do-Youn Jeong; Dong-Hwa Shin (Fermentation)
Gochujang, a traditional Korean fermented red pepper paste, is celebrated for its unique spicy and fermented flavor. This natural, whole food offers several health benefits due to the bioactive compounds formed during fermentation and its diverse ingredients. These bioactive compounds have been shown to have anti-cancer properties and anti-inflammatory effects by reducing inflammatory cytokines and suppressing pathways associated with diseases such as colitis and hepatitis. Gochujang has also been shown to help prevent obesity by promoting weight loss, inhibiting fat accumulation, and improving lipid profiles. It has also been shown to aid in the prevention of diabetes by suppressing hepatic glucose production and improving insulin sensitivity. The influence of gochujang on the gut microbiota is remarkable, with the ability to increase beneficial bacteria, improve microbial balance, and alleviate metabolic disorders. The primary agents responsible for these effects are capsaicin, fermentation by-products, and other bioactive compounds. The fermentation process, driven by microorganisms, enhances the nutritional and functional properties of gochujang, strengthening its health-promoting potential. This paper provides a comprehensive review of gochujang’s historical background, production methods, the role of microorganisms in fermentation, and its functional properties, emphasizing its value as a functional food for overall health improvement.